Academic achievements of medical student related to interactive problem-based learning in blended learning context - Troyanskaya, Marija; Garnova, Natalya; Filippova, Alla; Ustyuzhina, Olga; Pronkin, Nikolay (International Journal of Evaluation and Research in Education (IJERE), 2024)
The purpose of the current study is to prove the effectiveness of using interactive elements in problem-based learning (PBL) for medical students. The simultaneous use of interactivity and a problem-solving approach makes it possible to improve the pedagogy of distance learning and improve the training of medical specialties. In the study, 120 medical students of 4-5 university courses were enrolled, who were divided into 3 groups, a control group and two experimental ones, who received intervention one in the form of PBL, the second - PBL and also interactive elements in blended learning. Participants in the groups were randomly selected but with an equal representation of men and women aged 21 to 23 years. The results were measured using the university 12-point system and the presence of statistically significant differences was established using the student’s t-test. It was found that in experimental groups, the results of the post-test of academic achievement were statistically significantly higher than the pre-test. At the same time, the best changes were recorded in the group with PLB and interactive training at the same time. There were no statistically significant differences between genders within each group or between groups; however, females performed slightly better on average than males. Practically, the results of the study can be used to improve the academic training of physicians during distance learning and to improve practical problem-solving skills. The current study can be used in further analysis of PBL of medical students subject to the global integration of digital technologies in educational systems.